Solution-processed copper oxide interlayers for broadband PbS quantum-dot photodiodes. Issue 47 (16th November 2016) - Yu, Hyeonggeun; Liu, Shyui; Baek, Sujin; Kim, Do Young; Dong, Chen; So, Franky
Abstract : Metal oxide interlayers are promising for optoelectronic applications due to solution processability, optical transparency, and excellent charge blocking properties. Abstract : Metal oxide interlayers are promising for optoelectronic applications due to solution processability, optical transparency, and excellent charge blocking properties. Highly efficient, air-stable quantum dot photodetectors have been reported using solution-processed metal oxide interlayers. However, the processing temperatures are high, significantly limiting their potential for roll-to-roll processing. Here, we report low temperature-processed broadband PbS quantum dot photodiodes by employing a solution-processed CuO x interlayer. The resulting photodiodes exhibit a low dark current of 10 nA cm −2 with a detectivity over 10 13 Jones. Finally, we demonstrate a flexible inorganic photodiode on a polyethylene terephthalate substrate.